Arctic Hunter Gatherer beliefs in animal spirits as "Human relationships with the natural world which are embedded in the Arctic Hunter Gatherer Society and family roles (Erica Hill) as social consciousness in context of William James "Practical Use" Prin - Charles Peck Jr (Paleoceanography, 2008)
Erica Hill emphasizes, “Their thoughts and actions established and maintained relationships with prey animals and may be more productively conceptualized as dynamic social behaviours embedded within the context of daily life than as privileged ritual acts.” It would appear readily apparent that in many different ways spiritual and religious beliefs have become entangled in modern academic abstractions – number one being the stereotype that “All spirituality is unreal” – primarily because western academics are fixated with the “supernatural” according to Welsh Nobel prize winning scientist Brian Josephson – as opposed to fruitfulness. I might briefly mention the beliefs in "nature as force" in hunter-gatherer societies is consist with Mannheim’s “law” that the economic-political reality shaped social views. As Paloutzian and Park (p. 12, emphasis added) also contend, “religion and spirituality are more or less coherent, culturally elaborated meaning systems embedded in and acquired through social relationships and institutions situated in complex natural and built environments.” In Erica Hill’s very detailed and thorough article, Animals as Agents: Hunting Ritual and Relational Ontologies in Prehistoric Alaska and Chukotka, Erica Hill clearly highlights the fact that the issue in the spiritual beliefs in animal spirits, “human relationships with the natural world” is the pivotal issue. Essentially, Erica Hill defines spiritual beliefs in this context human relationships with the environment. The emphasis is on the “human relationships” – in contrast to relationships with the “supernatural.”